2020
DOI: 10.1002/ab.21912
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐induced aggression and changes in social behavior in mice

Abstract: The effects of neuropathic, formalin, and acetic acid‐induced visceral pain were investigated on the social and aggressive behaviors in the Swiss male mice. Neuropathic pain was induced by tibial nerve transection (TNT). Also, somatic and visceral pain was conducted by intraplantar injection of diluted formalin (1%, 20 μl) and intraperitoneal administration of acetic acid (0.6%, 200 μl), respectively. Fourteen and twenty one days after the TNT surgery, and also, 1 and 7 days following formalin and acetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(52 reference statements)
0
8
1
Order By: Relevance
“…The above results do not correlate with the available literature, because in neuropathic pain, aggression is described in both humans and in animals [ 6 , 46 ]. The frequency of its occurrence in cases of chronic pain is as high as 70% [ 8 ].…”
Section: Discussioncontrasting
confidence: 59%
“…The above results do not correlate with the available literature, because in neuropathic pain, aggression is described in both humans and in animals [ 6 , 46 ]. The frequency of its occurrence in cases of chronic pain is as high as 70% [ 8 ].…”
Section: Discussioncontrasting
confidence: 59%
“…These are confirmed by Allen et al, who stated that the pain and discomfort as situation factors could increase the likelihood of aggression in a general aggression model [ 20 ]. Indeed, mice models of Khosravi et al demonstrated that the mice with a present pain were not just more aggressive, but showed lesser attack latency than the control group [ 21 ]. We could add to these findings, i.e., in that the literature distinguishes between the stable and unstable patterns of aggression in children, where perpetrators with high pain tolerance could misperceive pain inflicted by another person, which would disinhibit aggressive action during conflict with others [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain also leads to aggressive behaviors. Compared with the control groups, mice with neuropathic, formalin, or acetic acid-induced visceral pain showed more aggressive behaviors like biting and clinching and had much less attack latency …”
Section: Lateral Habenula and Behaviors Associated With Painmentioning
confidence: 95%
“…Compared with the control groups, mice with neuropathic, formalin, or acetic acid-induced visceral pain showed more aggressive behaviors like biting and clinching and had much less attack latency. 7 It has already been reported that the LHb plays role in both pain and aggression. 32,69 Compared with that of nonaggressive male mice, the total number of c-fos + nuclei was reduced in the highly aggressive males, indicating global inactivation of the LHb.…”
Section: Lateral Habenula and Behaviorsmentioning
confidence: 98%
See 1 more Smart Citation